2008
DOI: 10.1111/j.1551-2916.2008.02313.x
|View full text |Cite
|
Sign up to set email alerts
|

Excimer Laser Crystallized (Pb,La)(Zr,Ti)O3 Thin Films

Abstract: A KrF pulsed excimer laser (248 nm) was utilized to crystallize sputtered La-modified Pb(Zr,Ti)O 3 (3:30:70) (PLZT) films on LaNiO 3 -coated silicon substrates. The film surface was irradiated with defocused laser pulses in an oxygen ambient at various substrate temperatures. Polycrystalline, phase pure perovskite PLZT thin films were produced for substrate temperatures of 2501C and higher. The dielectric constant and loss tangent values of laser-assisted crystallized (10 min exposure at 10 Hz using a substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…In this context, laser irradiation appears as a potential alternative because laser irradiation exhibits a significantly fast and localized thermal effect without any interference with the underlying substrates or surrounding circuitry. Many studies have been conducted on the laser irradiation of dielectric, ferroelectric, and piezoelectric ceramic films for different purposes . Representative findings of some of these studies on laser irradiated electroceramic films are discussed below.…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
“…In this context, laser irradiation appears as a potential alternative because laser irradiation exhibits a significantly fast and localized thermal effect without any interference with the underlying substrates or surrounding circuitry. Many studies have been conducted on the laser irradiation of dielectric, ferroelectric, and piezoelectric ceramic films for different purposes . Representative findings of some of these studies on laser irradiated electroceramic films are discussed below.…”
Section: Laser Irradiation Of Metal Oxides and Their Applicationsmentioning
confidence: 99%
“…UV activation has been implemented to promote decomposition of functional groups in the as-deposited films [6]. Beside introducing previously mentioned nucleation layers or seeds [7], laser activation has been reported to decrease the crystallization temperature of thin films [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, direct integration of the piezoelectric thin film with a microchip would improve response times in sensors, potentially coupled with low‐cost manufacturing . Pulsed‐laser treatment is one way to selectively heat the film to achieve the high temperatures required for perovskite phase crystallization, while causing minimal heating of the underlying substrate …”
Section: Introductionmentioning
confidence: 99%
“…3 Pulsed-laser treatment is one way to selectively heat the film to achieve the high temperatures required for perovskite phase crystallization, while causing minimal heating of the underlying substrate. [4][5][6][7][8][9][10] Moreover, in situ heat treatment of oxide thin films during growth can also benefit from reduced crystallization temperatures compared to a postdeposition thermal processing. 11,12 It has been shown that crystallization of ferroelectric thin films can be achieved by simultaneous laser annealing during growth at substrate temperatures of ≤400°C.…”
Section: Introductionmentioning
confidence: 99%